Динаміка семантичної структури лексем буда, хороми - Солодка, С. (Лексикографічний бюлетень, 2011)
The article deals with semantic structure of lexemes buda and khoromy, fixed in the historical, etymologic and dialectal dictionaries of the Ukrainian; the dynamics of semantic structure of the analyzed words in the Ukrainian language is highlighted, most attention has been paid to changing their semantics from the first fixing by writing sights to our time; taking into account etymology of lexemes buda and khoromy, and certainly their primary meaning; factors causing semantic structure development have been found out. It has been stated, that the analyzed lexemes have complex semantic structure, development of which deals with the internal form of these words, their primitive meaning, expansion of meaning, stratification of the newest senses.